Mengkomunikasikan Pendidikan dan Melestarikan Kearifan Lokal Orang Bajo - Mukti Ali (State Institute of Islamic Studies (IAIN) Salatiga, 2017)
This research used ethnographic method on sea tribe, a sub-culture of Indonesian society commonly known by anthropologists with the term of the Bajo Tribe. The educational phenomenon of Bajo society has uniqueness, besides acknowledging that they only know, believe, and guided by the Islamic system, but in carrying out the main rituals of Islamic teachings are not visible, so is their awareness to go to higher education is very difficult to realize in the understanding of society. For the People of Orang Bajo, education should not be lost from a value taught from generation to generation, and should not be lost from the life of their grandchildren. While formal education can be done enough for primary school (SD) only. Even if they can continue their education to a higher level, they are simply maintaining their values or education based on their local cultural wisdom. There are various findings of local wisdom that became the education identity of Bajo are Kampoh or togetherness in village, Lukka maintain the tradition of marriage, and Alla Tala have confidence in the power of God.